2021
DOI: 10.3390/ijms23010002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Ovarian Aging Is Associated with Altered Expression of Post-Translational Modifications in Mice

Abstract: Post-translational modifications (PTMs) have been confirmed to be involved in multiple female reproductive events, but their role in physiological ovarian aging is far from elucidated. In this study, mice aged 3, 12 or 17 months (3M, 12M, 17M) were selected as physiological ovarian aging models. The expression of female reproductive function-related genes, the global profiles of PTMs, and the level of histone modifications and related regulatory enzymes were examined during physiological ovarian aging in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A progressive increase in the expression levels of both Suv4-20h1 and Suv4-20h2 has been reported during physiological ovarian aging in mice [45]. However, whether this increase is accompanied by augmented H4K20me3 levels is not known.…”
Section: Agingmentioning
confidence: 99%
“…A progressive increase in the expression levels of both Suv4-20h1 and Suv4-20h2 has been reported during physiological ovarian aging in mice [45]. However, whether this increase is accompanied by augmented H4K20me3 levels is not known.…”
Section: Agingmentioning
confidence: 99%
“…To perform hematoxylin-eosin (HE) staining, 5-µm sections were obtained and stained using the HE staining procedure (Baso, China). The maximum section in each tissue was selected for microscopic (Nikon Ci-S, Japan) observation on the pathological structure of tissue and photography, following previously established protocols ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, our previous study revealed that the global Ksuc in mouse ovary increases signi cantly with advancing age [12]. Thus, in this study we further evaluated the effect of excessive Ksuc on ovarian function to reveal the relationship between Ksuc and ovarian aging.…”
Section: Introductionmentioning
confidence: 92%